Strategi Jitu Blue Ocean Menciptakan Peluang Industri Pariwisata Tanpa Persaingan di Provinsi Bangka Belitung - Sultan Ilhamsyah; Vindi Nurmala Dewi; Veronica Ruth Rohani Siburian; Indah Noviyanti (Pusat Riset dan Inovasi Nasional, 2024)
Blue Ocean Strategy offers a transformational opportunity for the tourism industry to escape fierce competition and explore new, unexplored markets. The research method used is a qualitative method based on literature studies from previous research, by evaluating and analyzing relevant scientific journals. To implement Blue Ocean Strategy effectively, there are several tools and frameworks that can be used, such as the Blue Ocean Strategy Canvas and the ECRR Blue Ocean Strategy concept. In order to create opportunities for the tourism industry without competition, a situation analysis was carried out using SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats) to understand the current position of Bangka Belitung. Natural beauty is one of the strengths that can be developed in developing tourism in Bangka Belitung. Apart from that, it is also necessary to identify new market opportunities such as ecotourism, local culture or unique adventures. Through the application of the Blue Ocean Strategy and its principles, the Bangka Belitung tourism industry has the potential to create a unique and unexplored new market.